Role of a micronized purified flavonoid fraction as an adjuvant treatment to rubber band ligation for the treatment of patients with hemorrhoidal disease: a longitudinal cohort study - Caetano, Ana Célia (2019)
Nonsurgical treatment of hemorrhoidal disease (HD) includes medical and instrumental techniques. We aimed to compare the efficacy of the most frequently used nonsurgical strategies, either alone or in combination, applied in an ambulatory setting. Purpose: Nonsurgical treatment of hemorrhoidal disease (HD) includes medical and instrumental techniques. We aimed to compare the efficacy of the most frequently used nonsurgical strategies, either alone or in combination, applied in an ambulatory setting. Methods: Patients who received nonsurgical treatment for HD by proctology appointment at the Gastroenterology Department of Braga Hospital were evaluated. Isolated rubber band ligation (RBL) and a combination of RBL with a micronized purified flavonoid fraction (MPFF) were the 2 most frequently used strategies. Symptoms of HD (bleeding, pruritus, pain at rest, pain at defecation and prolapse) were assessed at days 0, 7, and 28 by using a severity grading scale (0 to 4/5). A Global Symptom score was constructed to assess the overall severity and compare the overall improvements of the HD symptoms between the 2 most frequently used strategies. Results: Nineteen patients underwent the combined treatment (RBL + MPFF group) and 25 the RBL treatment (RBL group). A comparison of the 2 treatment groups showed significant improvements in the combined treatment group in terms of bleeding at days 7 (P = 0.001) and 28 (P = 0.002) and in the pruritus intensity during the first week (P < 0.001). A trend toward clinical benefit was also verified in the combined treatment group for all other HD symptoms (pain at rest, pain at defecation and prolapse). Conclusion: A combined treatment approach with MPFF and RBL significantly reduced the intensity of bleeding during the first month and the pruritus during the first week